PEMBUATAN MATERIAL MAGNETIK KOMPOSIT BaFe9Mn0,75Co0,75Ti1,5O19/ELASTOMER UNTUK APLIKASI PENYERAP GELOMBANG ELEKTROMAGNETIK - Windu Ganar Prasongko; Priyono Priyono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The magnetic material of BaFe12 - 2x ( MnCo ) xTixO19 which is considered as a magnetic material of M type Hexaferrite and being substituted partially of two Fe3+ ions with an Mn 2+ ion , Co2+ , and an Ti4+ ion has been researched and tested by using sol gel method. The magnetic material is formed from Ba( NO3 )2 , Fe( NO3 )2 , Mn( NO3 )2 , Co( NO3 )2 , Ti( NO3 )4.BaFe12 - 2x( MnCo )xTixO19 for x = 1.5 synthesized by using sol gel, in the form of powder. From the magnetic test result, it is obtained that the coercivity values is 3.8 kA / m and the magnetization value is 0.29 Tesla. The density test result of pellet barium heksaferrite is 3.453 to 5.060 g / cm3 for 90 μm. The morphology analysis of the sample surface by using Scanning Electron Microscopy( SEM ) showed hetereogenety in particle size. The result of absorption test showed the absorption in the range of 8-12 GHz. The result of mechanical tests showed that the adhesion test had the variation values to different point.Keywords: BaFe12 - 2x( MnCo )xTixO19 for x = 1.5,sol gel